Optimization of intraoperative ultrasound navigation during focal cortical dysplasia surgery: a case report - K. Simfukwe; A. A. Suﬁanov (Сеченовский вестник, 2022)
Intraoperative ultrasound (IUS) is known to be an effective method for neuronavigation during surgical treatment of intractable seizures caused by focal cortical dysplasia (FCD). However, the 2-dimensional (2D) IUS has poor image quality and low spatial resolution. We describe via a case report how Ultrasound integrated Brainlab (BL) – Navigation software was used to optimize 2D IUS and thereby reduce these challenges.Case report: We present a case report of a 22-year-old female patient with a long-standing history of seizures. The patient was treated with more than two anti-epileptic drugs without any clinical efﬁcacy. In 2022 she was diagnosed with temporal lobe FCD. We performed a temporal lobe lesionectomy using optimized IUS BL-Navigation that provided enhanced 3-dimensional (3D) images.Discussion: The extent of resection of the underlying FCD lesion is a key factor in determining whether a patient achieves meaningful seizure freedom after surgery. While the 2D IUS offers admirable characteristics that have been used as an aid during surgery, it is our view that IUS enhanced 3D BL-Navigation offers better appreciation of FCD lesions and therefore improves the extent of resection.